Dengue Vulnerability Mapping Using AHP and Weighted Overlay Method: A Case Study from Bandar Lampung City, Indonesia - Winalia Winalia; Prayudhy Yushananta; Mei Ahyanti (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2026)
Dengue fever remains a serious health problem due to its high morbidity and mortality. Given its potential future impacts, vulnerability maps are needed to guide the design of evidence-based control strategies. This study aims to develop a dengue fever vulnerability map by combining the AHP and weighted overlay techniques. This study used an ecological design and was conducted in Bandar Lampung City, Lampung Province. All secondary data were aggregated into percentages and used as sub-districts as spatial boundaries. The AHP method involved 20 informants to determine the weight of each variable (population density, water storage facilities, house index, and 3M behavior). The weighting results served as a reference for developing a dengue fever vulnerability map using the weighted overlay technique. Risk categories are distinguished by green (low), yellow (medium), and red (high). The AHP yielded the following weighted values for each variable: 30% (house index), 28.3% (3M behavior), 23.2% (water storage facilities), and 18.5% (population density). Based on the weighted overlay technique, five high-risk sub-districts were obtained (East Tanjungkarang, North Telukbetung, South Telukbetung, Bumi Waras, and Panjang), five medium-risk sub-districts (Langkapura, Kedaton, Central Tanjungkarang, Enggal, and East Telukbetung), and ten low-risk sub-districts (Rajabasa, Tanjung Senang, Labuhan Ratu, Sukarame, Kemiling, West Tanjungkarang, Way Halim, Kedamaian, Sukabumi, and West Telukbetung). GIS applications by combining the AHP and weighted overlay methods can be applied to develop dengue fever vulnerability maps.